The Crisis of Humanism in the Character Ismail al-Sheikh in Najib Mahfouz’s Novel al-Karnak: A Humanistic Psychology Study - Reza, Muhammad; Zulhelmi; A’la, Al Farahil (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2026)
This study aims to examine the crisis of humanistic values in the novel Al-Karnak by Najib Mahfouz, which portrays the psychological impact of repressive actions by the government in Egypt through the lens of Abraham Maslow's humanistic theory. The methodology employed in this study is qualitative descriptive, with data collection techniques including reading and note-taking, literature review, as well as careful reading and manual coding. The data obtained in this study are analyzed using data analysis techniques involving identification, classification, analysis, and drawing conclusions. This research provides a new perspective by focusing on the humanism crisis of the character Ismail Al-Syaikh, who is a figure in Al-Karnak. Research findings reveal that in Al-Karnak there is a crisis of humanism, manifested in the failure to meet the hierarchy of human needs according to Abraham Maslow, which includes physiological needs, safety, love and belonging, esteem, and self-actualization. At the physiological level, characters experience physical suffering due to torture. At the safety level, characters are surrounded by fear caused by threats and violence. At the love and belonging level, social relationships among characters face problems. At the esteem level, characters lose self-confidence and dignity. On the other hand, at the self-actualization level, characters struggle to develop their potential and lose their sense of direction in life.